Does Stakeholder Management have a Dark Side? - Cennamo, Carmelo (Journal of business ethics, 2009)
This article is a first attempt to line out the conditions under which executives might have a real self-interest in pursuing a broad stakeholder management (SM) orientation to enlarge their power. We suggest that managers have wider latitude of action under an SM approach, even when this is instrumental to financial performance. The causally ambiguity of the performance effects of idiosyncratic relationships with stakeholders not only makes SM strategy difficult for competitors to imitate but also increases managerial discretion. When managers use this situation for their own benefit, they can undermine the purported goals of the SM approach. By analyzing some of the factors that might lead to such disfunctionalities, this article advances a theory of the potential dark side of SM.